Bridge helix and trigger loop perturbations generate superactive RNA polymerases - Tan, Lin (BioMed Central, 2008)
BACKGROUND: Cellular RNA polymerases are highly conserved enzymes that undergo complex conformational changes to coordinate the processing of nucleic acid substrates through the active site. Two domains in particular, the bridge helix and the trigger loop, play a key role in this mechanism by adopting different conformations at various stages of the nucleotide addition cycle. The functional relevance of these structural changes has been difficult to assess from the relatively small number of static crystal structures currently available. RESULTS: Using a novel robotic approach we characterized the functional properties of 367 site-directed mutants of the Methanocaldococcus jannaschii RNA polymerase A' subunit, revealing a wide spectrum of in vitro phenotypes. We show that a surprisingly large number of single amino acid substitutions in the bridge helix, including a kink-inducing proline substitution, increase the specific activity of RNA polymerase. Other 'superactivating' substitutions are located in the adjacent base helices of the trigger loop. CONCLUSION: The results support the hypothesis that the nucleotide addition cycle involves a kinked bridge helix conformation. The active center of RNA polymerase seems to be constrained by a network of functional interactions between the bridge helix and trigger loop that controls fundamental parameters of RNA synthesis.